NONLINEAR CONTACT ANALYSIS OF THE MIDDLE PAN DUMBBELL PIN SCRAPER CONVEYOR - ZHANG DongSheng; YU HaiYang; JIANG JiaNing; HU DengGao (Jixie qiangdu)
In this paper,the research of the scraper conveyor is carried out,the force analysis of the adjacent middle pan group and the dumbbell pin is carried out,and the dumbbell pin load data is obtained by the dumbbell pin load test system. The ANSYS/ls-dyna software is used to simulate the nonlinear contact dynamics of the middle pan group and the dumbbell pin under the push-slip condition of the scraper conveyor. The contact stress of the dumbbell pin is the largest,and the maximum contact stress of the dumbbell pin occurs at the abrupt change of the dumbbell pin section,and the maximum contact stress of the dumbbell pin And the contact stress concentration between the two middle slots occurred at the joints of the dumbbell pin and the middle ditch. The simulation results were in accordance with the actual working conditions. This study provides a dumbbell pin load test program,and through the test simulation to verify its correctness and feasibility,while the middle slot and dumbbell pin structure size optimization method.